IMPLEMENTASI SISTEM INFORMASI QUALITY CONTROL PRODUK BERRBASIS WEBSITE - Uliyatunisa Uliyatunisa (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In the course of its production, one of the main tasks that largely determines the process of Quality Control of products that have been approved before being marketed to consumers in order to minimize receiving errors or malfunctions of these products. For that the company needs an application that can repair the damaged production process from Quality Control directly to the production department. Company owners will be able to directly control their production directly. The system is made using a website by collecting research using a waterfall. While the analysis is done by interviewing and surveying the system that is run to get the information needed. The results obtained from this study are that the process reported from failed production from the Quality Control division to the production division becomes faster and is well approved by the company which can directly control and analyze the production as an indicator of production effectiveness and improve the quality control staff according to the product QR Code generated is made differently on each product so as to minimize the recording of existing damage data